Structure and expression of genes for surface proteins in Paramecium. - Forney, J D (1983)
Surface proteins from 11 antigenic types of Paramecium tetraurelia vary in molecular weight from 251,000 to 308,000. The size of a series of polyadenylated RNAs obtained from these types were correlated with the sizes of the proteins and judged to be the mRNAs for the proteins. The mRNAs were used to identify genomic DNA clones containing complementary sequences. The gene for antigen A was present in one copy per genome, and the data suggest that extensive introns were absent. When restriction enzyme digests of DNA from cultures of paramecia with active and inactive genes were probed with portions of the cloned genes, no evidence for rearrangements or changes in gene dosage was found.